The Jepara Chairs Based on Their Style and Period - Octaviana S.C. Rombe; Yunida Sofiana; Bambang Kartono Kurniawan; Oktavianus Marti Nangoy (Humaniora, 2016)
The purpose of this article was to identify the Jepara chairs based on its style and period. Qualitative research such as doing interviews with the Jepara chairs observer, observation to some centres and workshops of Jepara chairs, literature study from various books consisting the style and process of Jepara chairs production were conducted. The identification of Jepara chairs started with Islamic and Hinduism influence in the 16th to the 17th century when the missionary and sailor from Portuguese entered Java until the style of Jepara chair in the 20th century. The alteration that mirrors the changes in socio-cultural aspect was being analysed as the style foundation that was used periodically in the making of the Jepara chairs. The categories a chair to have a Jepara style is a chair made by the craftsman in Jepara that, includes local factors both technically and material based that is combined with foreign culture, religion, and designs that brought at the time the chairs have been made. This research finds that chairs with Jepara style are a combination of the international world with a glimpse of local wisdom, with a touch of the maker’s personality that makes it unique and a bit different with its origin style.